Status keluhan penyakit kulit santri Pesantren Al Ikhlas, Kabupaten Bone, Provinsi Sulawesi Selatan - Andi Irhamnia Sakinah; Andi Faradilah; Fhirastika Annisha Helvian (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2020)
The status of skin diseases complaints of the students at the Al Ikhlas Islamic Boarding School, Bone Regency, South Sulawesi Province. Skin diseases are the most common problems among students. Hygiene factors play an important role in the emergence of skin diseases in Islamic boarding schools. In the community service activities of the Medical Education Study Program of the Faculty of Medicine and Health Sciences, we aim to carry out examinations and interventions for treatment and counseling related to skin diseases that are often found in students of Islamic boarding school. Community service activities were carried out on 96 students who all followed all stages, namely counseling, skin examinations, and treatment. The complaints of itching reaching a prevalence of 87.5% were expressed by students while complaints in the form of head lice and dandruff were dominant only by female students (santriwati). Complaints of skin disease are still a frequent complaint among students of Islamic boarding school. Community service activities at Islamic boarding school with the theme of skin and venereal diseases need to be more encouraged.